2020
DOI: 10.1080/10350330.2020.1767399
|View full text |Cite
|
Sign up to set email alerts
|

Selling surveillance technology: semiotic themes in advertisements for ageing in place with dementia

Abstract: Six advertisements were explored that sell surveillance technologies for people living with dementia through qualitative content analysis.Advertisements from the United Kingdom, Sweden and the Netherlands were analysed to explore semiotic textual meaning and people with dementia (N=5) and carers (N=4) responded to these advertisements. The semiotic themes report a "wanderer" discourse which signals to track people living with dementia, children pets and possessions. Mainly negative representations communicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 52 publications
(69 reference statements)
0
7
0
Order By: Relevance
“…Feedback on the presented advertisement yers indicated that product marketing has a large room for improvement in terms of content and visuals. Similar to recent studies (42,43), professionals' stressed the importance of placing end-users at the center of marketing activities to reduce stigmatizing keywords and visuals, as well as to ensure that information on functionality and data security are transparently and adequately addressed.…”
Section: Discussionmentioning
confidence: 74%
“…Feedback on the presented advertisement yers indicated that product marketing has a large room for improvement in terms of content and visuals. Similar to recent studies (42,43), professionals' stressed the importance of placing end-users at the center of marketing activities to reduce stigmatizing keywords and visuals, as well as to ensure that information on functionality and data security are transparently and adequately addressed.…”
Section: Discussionmentioning
confidence: 74%
“…Between September 2021 and March 2022, the author collected data through an online search for AgeTech advertisement videos for ageing-in-place technologies that were posted online between the years 2015 and 2022. Similar to semiotic analysis of AgeTech YouTube videos by Vermeer et al ( 2020 ), the author used the video search function on the Google search engine to locate videos on YouTube. The search targeted specific AgeTech companies that had been identified in a previous research project about design of technologies for ageing-in-place among prominent companies that market ambient monitoring systems for older adults.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, the messages were directed at families and care providers, rather than people living with dementia, who were dehumanised in their portrayal as a “problem to be managed” and categorised “in the same class as wallets, keys, young children, dogs and/or prisoners” (Vermeer et al, 2019 , p. 27). Follow-up research by Vermeer et al ( 2020 ) framed online advertisements for dementia-focused surveillance technologies as cultural texts that shaped audience perceptions about dementia and the impact that dementia has on others. This foundational research carefully analysed the content of YouTube advertisements, looking at the combination of visual representation and spoken language.…”
Section: Representations Of Older Age In Agetech Advertisingmentioning
confidence: 99%
See 1 more Smart Citation
“…Semiotics is a way to recognize what signs and meanings are used in advertisements through a textual approach. De Saussure introduced semiotics as the relationship between language and meaning through signifiers and signified (Vermeer et al, 2020).…”
Section: Methodsmentioning
confidence: 99%